2007
DOI: 10.1002/cm.20243
|View full text |Cite
|
Sign up to set email alerts
|

Tau inhibits anterograde axonal transport and perturbs stability in growing axonal neurites in part by displacing kinesin cargo: Neurofilaments attenuate tau‐mediated neurite instability

Abstract: Overexpression of tau compromises axonal transport and induces retraction of growing neurites. We tested the hypothesis that increased stability provided by neurofilaments (NFs) may prevent axonal retraction. NB2a/d1 cells were differentiated for 3 days, at which time phosphorylated NFs appear and for 14 days, which induces continued neurite elongation and further phospho-NF accumulation. Cultures were transfected with a construct that expresses full-length, 4-repeat tau. Consistent with prior studies, overexp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
69
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(78 citation statements)
references
References 45 publications
7
69
0
1
Order By: Relevance
“…Failure to properly distribute mitochondria throughout the cell leaves synapses deprived of their energy requirements, susceptible to reactive oxygen species, and with inefficient calcium handling and can result in synaptic dysfunction and subsequent dying back of the neuron. 15,19,20,53 When improperly distributed, mitochondria are thought to have impaired function 25,54 and this can lead to increased neuronal susceptibility to excitotoxicity or neurodegenerative stressors such as amyloid-␤. 2 Changes to mitochondrial distribution have been linked to failure to maintain mitochondrial membrane potential, resulting in release and activation of pro-apoptotic molecules such as caspase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Failure to properly distribute mitochondria throughout the cell leaves synapses deprived of their energy requirements, susceptible to reactive oxygen species, and with inefficient calcium handling and can result in synaptic dysfunction and subsequent dying back of the neuron. 15,19,20,53 When improperly distributed, mitochondria are thought to have impaired function 25,54 and this can lead to increased neuronal susceptibility to excitotoxicity or neurodegenerative stressors such as amyloid-␤. 2 Changes to mitochondrial distribution have been linked to failure to maintain mitochondrial membrane potential, resulting in release and activation of pro-apoptotic molecules such as caspase.…”
Section: Discussionmentioning
confidence: 99%
“…8 -12 Meanwhile, tau overexpression, which results in abnormally high levels of soluble tau throughout the cell in the absence of aggregates, alters fast axonal transport, particularly in the anterograde or kinesin-dependent direction. [13][14][15][16][17][18] This transport deficit is thought to lead to depletion of necessary materials, deterioration of the synapse, and a "dying back" of the neuron. 19 -21 We previously found in cultured neurons that alterations in axonal transport due to soluble tau over-expression resulted in perinuclear clumping of mitochondria.…”
mentioning
confidence: 99%
“…Many reports have described the inhibition of mitochondrial transport by overexpressing Tau (Ebneth et al, 1998;Trinczek et al, 1999;Stamer et al, 2002;Dixit et al, 2008;Dubey et al, 2008;Stoothoff et al, 2009;Vossel et al, 2010). However, the molecular mechanism has not been determined.…”
Section: Discussionmentioning
confidence: 99%
“…Among the different ways Tau might affect MAPK signaling are interactions with signaling protein complexes or alterations in microtubule-dependent growth factor receptor trafficking to the cell surface. Studies performed in vitro and in cells have suggested a role for Tau in axonal transport and vesicle trafficking where it has been found that the presence of Tau inhibited transport (57)(58)(59)(60)(61)(62)(63), whereas another study carried out in mice reported that the Tau level had no effect on transport (64). Based on these findings, one would not predict that Tau depletion would inhibit vesicle transport or lead to decreases in growth factor receptors (e.g.…”
Section: Discussionmentioning
confidence: 99%